2017
DOI: 10.1007/s12603-017-0939-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival in malnourished older patients receiving post-discharge nutritional support; long-term results of a randomized controlled trial

Abstract: The current study failed to show an effect of a three-months post-discharge multi-component nutritional intervention in malnourished older patients on long-term survival, despite the positive effects on short-term outcome such as functional limitations and falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Lindhardt et al [28] provided participants with an internet-enabled tablet, preloaded with an application which allowed them to order meals three times per week, and provided automated feedback on how intake corresponded with individual energy and protein requirements. Only one intervention, reported across four publications by Neelemaat et al [34,[37][38][39], provided all participants with oral nutritional supplements; whereas five other studies provided them on a case-by-case basis to align with an individualised plan [27,30,32,33,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Lindhardt et al [28] provided participants with an internet-enabled tablet, preloaded with an application which allowed them to order meals three times per week, and provided automated feedback on how intake corresponded with individual energy and protein requirements. Only one intervention, reported across four publications by Neelemaat et al [34,[37][38][39], provided all participants with oral nutritional supplements; whereas five other studies provided them on a case-by-case basis to align with an individualised plan [27,30,32,33,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…In addition costeffectiveness of the intervention was shown [64]. No effects were found regarding body weight, fat free mass, handgrip strength as well as 1-and 4-year mortality [63,65]. Beck et al [66,67] conducted a multi-facet intervention in nursing home residents consisting of home-made nutritional supplements, oral care and group exercise resulting in improved protein intake, body weight, physical performance and social activity.…”
Section: Recommendation 9 Commentarymentioning
confidence: 99%
“…Seven studies reported hospital LOS. 21,22,24,26,27,29,33 Figure 3B shows the meta-analysis of the pooled effect size for LOS 21,24,27,29,33,37 (mean difference: −0.75 days; 95% CI, −1.66 to 0.17; I 2 = 70%; P = 0.11; GRADE: low certainty). Removing one study 29 (in which the mean LOS was calculated from median with IQR) reduced the heterogeneity to 27% but made little difference to the mean difference.…”
Section: Hospital Losmentioning
confidence: 99%
“…Sixteen studies 16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] met the inclusion criteria of our review and underwent data extraction. We also included data from the five post hoc study publications [34][35][36][37][38] by Neelemaat et al, 26 Scheutz et al, 27 and Söderström et al, 30 as they contained outcome data relevant to this meta-analysis. 28,32 The study characteristics are depicted in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation